Transformasi Peran Guru Muda dalam Inovasi Pembelajaran Teknologi di Sekolah Dasar Pasca Pandemi - Nila Rahayu Putri; Willy Akmansyah Lubis (An-Nuha, 2023)
This study aims to explore the transformation of young teachers' roles in implementing digital learning innovations in elementary schools post-COVID-19 pandemic. Using a descriptive qualitative approach at SDN 086 Dalan Lidang, Mandailing Natal, this research involved fourth-grade teachers as key informants. Data were collected through interviews, observations, and documentation, then analyzed using reduction, data display, and conclusion-drawing techniques. The results indicate that young teachers have transformed from conventional instructors into facilitators, instructional designers, and digital agents of change. Implemented innovations include the use of interactive media, digital quizzes, and the integration of educational videos, which have significantly increased student participation. The primary challenges identified are limited school infrastructure and gaps in students' digital literacy. However, the teachers' strategy of balancing technology with students' socio-emotional needs through collaborative learning and a humanistic approach remains the key to successful educational adaptation in the 21st-century era.